2017
DOI: 10.1007/s00203-017-1370-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization and transcriptional analysis of icd2 gene encoding an isocitrate dehydrogenase of Xanthomonas campestris pv. campestris

Abstract: Isocitrate dehydrogenase (IDH) catalyzes the oxidative decarboxylation of isocitrate to alpha-ketoglutarate. In the genome of Xanthomonas campestris pv. campestris, the phytopathogen that causes black rot in cruciferous plants, two putative IDH genes, icd1 and icd2, have been annotated. Their physiological roles in X. campestris pv. campestris are unclear. In this study, the icd2 gene from X. campestris pv. campestris was characterized in detail. We demonstrated genetically that icd2 gene encodes a functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…As several factors having a role in bacterial attachment have been reported to involved in pathogenicity in X. campestris pv. campestris [10, 11, 13, 14], we aimed to determine whether the lolA mutation affected the virulence of X. campestris pv. campestris .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As several factors having a role in bacterial attachment have been reported to involved in pathogenicity in X. campestris pv. campestris [10, 11, 13, 14], we aimed to determine whether the lolA mutation affected the virulence of X. campestris pv. campestris .…”
Section: Resultsmentioning
confidence: 99%
“…In X. campestris pv. campestris , several factors reported to influence biofilm formation and bacterial adhesion also have roles in pathogenicity, namely extracellular mannanase ManA [6], GGDEF domain protein XC_0249 [9], guanylate cyclase XC_0250 [9], isocitrate dehydrogenase encoded by icd2 [10], major outer membrane protein MopB [11], the RavA/RavR two-component system [12], tail-specific protease encoded by prc [13], and UTP-glucose-1-phosphate uridylyltransferase encoded by galU [14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CRYL1 has been shown to be highly expressed in mammalian livers and kidneys, organs directly involved in lipid metabolism (Chen et al, 2003), and thus this gene in SEL BSF may fulfil a similar role, particularly during the feeding period of this species. Additionally, the gene isocitrate dehydrogenase 1 ( IDH1 , LOC119648135) encodes a rate‐limiting enzyme in the tricarboxylic acid cycle which is involved in cellular energy metabolism (Chiang et al, 2017), and has shown evidence that expression of this gene fulfils a protective function, supressing intracellular and mitochondrial reactive oxidative stress levels (Yang et al, 2017). Increased expression of both of these genes (among others) in SEL F3 larvae (Figure 10) in conjunction with significant positive correlations with larval mass (Table S6) illustrates the functional metabolic shift in this experimental line.…”
Section: Discussionmentioning
confidence: 99%
“…Since several factors playing a role in bacterial attachment are involved in pathogenicity in Xcc [12][13][14]17,18], we aimed to determine whether the wxcX gene is associated with the virulence of Xcc. The wxcX mutant revealed reduced virulence compared with the wild type (Fig.…”
Section: Wxcx Is Required For the Full Virulence Of Xccmentioning
confidence: 99%
“…The role of biofilm formation in the virulence of plant pathogenic bacteria has been reported for a range of bacterial infections in plants, such as Erwinia amylovora , the causal agent of fire blight, as well as Xylella fastidiosa , the causal agent of oak leaf scorch . In Xcc, several factors having a role in biofilm formation or bacterial adhesion are involved in virulence, including exopolysaccharide , extracellular mannanase ManA , GGDEF domain proteins XCC2731 and XC_0249 , guanylate cyclase XC_0250 , isocitrate dehydrogenase encoded by icd2 , major outer‐membrane protein MopB , RavA/RavR two‐component system , RNA‐binding protein RsmA , tail‐specific protease encoded by prc , and UTP‐glucose‐1‐phosphate uridylyltransferase encoded by galU .…”
Section: Introductionmentioning
confidence: 99%